Are rest intervals between stretching repetitions effective to acutely increase range of motion? - Freitas, S. R.; Vaz, J. R.; Bruno, P. M.; Valamatos, M. J.; Andrade, R. J.; Mil-Homens, P. (International Journal of Sports Physiology and Performance, 2015)
Static stretching with rest between repetitions is often performed to acutely increase joint flexibility. Purpose: To test the effects of the lack of resting between stretching repetitions and the minimal number of stretching repetitions required to change the maximal range of motion (ROM), maximal tolerated joint passive torque (MPT), and submaximal passive torque at a given angle (PT). Methods: Five static stretching repetitions with a 30-s rest-interval (RI) and a no-rest-interval (NRI) stretching protocol were compared. Participants (N = 47) were encouraged to perform the maximal ROM without pain in all the repetitions. Each repetition lasted 90 s. Maximal ROM, MPT, PT, and muscle activity were compared between protocols for the same number of stretching repetitions. Results: The NRI produced a higher increase in maximal ROM and MPT during and after stretching (P < .05). PT decreased in both protocols, although the NRI tended to have a lower decrement across different submaximal angles (.05 < P < .08) in the initial range of the torque-angle curve. Significant changes in maximal ROM (P < .01) and PT (P < .01) were obtained at the 3rd and 2nd repetitions of RI, respectively. The RI did not significantly increase the MPT (P = .12) after stretching; only the NRI did (P < .01). Conclusions: Lack of rest between repetitions more efficiently increased the maximal ROM and capacity to tolerate PT during and after stretching. The use of 30 s rest between repetitions potentiates the decrease in PT. Rest intervals should not be used if the aim is to acutely increase maximal ROM and peak passive torque.